2009
DOI: 10.1111/j.1600-0560.2008.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in QSART and vasoactive intestinal polypeptide expression in the skin of Parkinson’s disease patients and its relation to dyshidrosis

Abstract: Reduction in QSART and VIP expression in the sweat glands might be involved in the dyshidrosis of PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Reduced uptake in MIBG scintigraphy strongly pinpoints toward a degeneration of peripheral sympathetic neurons (Satoh et al, ). Moreover, peripheral impairment of sudomotor function measured by QSART could be detected in PD patients (Kawada et al, ) showing pathological values even in very early stages (Oh, Lee, Seo, Sohn, & Lee, ). Moreover, postmortem analysis revealed a severe degeneration of tyrosine hydroxylase positive noradrenergic peripheral axons in PD (Amino et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced uptake in MIBG scintigraphy strongly pinpoints toward a degeneration of peripheral sympathetic neurons (Satoh et al, ). Moreover, peripheral impairment of sudomotor function measured by QSART could be detected in PD patients (Kawada et al, ) showing pathological values even in very early stages (Oh, Lee, Seo, Sohn, & Lee, ). Moreover, postmortem analysis revealed a severe degeneration of tyrosine hydroxylase positive noradrenergic peripheral axons in PD (Amino et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been only a few studies using this method, indicating reduced53 and normal axon reflex sweating 54…”
Section: Autonomic Testsmentioning
confidence: 99%
“…The impulse then travels orthodromically down that axon to evoke a sweat response which is recorded. In PD patients with confirmed sympathetic cardiac denervation, the QSART was found to be normal suggesting selective loss of post-ganglionic catecholaminergic but not cholinergic nerves[35], while another study found QSART responses to be lower in PD compared to controls[36]. Skin sympathetic peroneal nerve activity has also been found to be lower in PD compared to controls[37], suggesting postganglionic sympathetic sudomotor lesions in PD.…”
Section: Skin and Sweat Glandsmentioning
confidence: 99%